Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Our platform connects you with professionals ready to provide precise answers to all your questions in various areas of expertise. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

Solve the system of equations:

[tex]\[
\begin{cases}
x + 2y - z = 3 \\
2x + 4y - 2z = 6 \\
-x - 2y + 2z = 6
\end{cases}
\][/tex]


Sagot :

Let's solve the given system of linear equations step-by-step:

[tex]\[ \begin{aligned} &1.\quad x + 2y - z = 3 \quad \text{(Equation 1)} \\ &2.\quad 2x + 4y - 2z = 6 \quad \text{(Equation 2)} \\ &3.\quad -x - 2y + 2 = 6 \quad \text{(Equation 3)} \\ \end{aligned} \][/tex]

First, let's simplify Equation 3:

[tex]\[ -x - 2y + 2 = 6 \implies -x - 2y = 4 \implies x + 2y = -4 \quad \text{(Equation 4)} \][/tex]

Next, let's observe Equations 1 and 2. Notice that Equation 2 is simply twice Equation 1:

[tex]\[ 2(x + 2y - z) = 2 \cdot 3 \implies 2x + 4y - 2z = 6 \][/tex]

This means that Equation 2 does not provide any new information and is redundant.

Hence, we are left with two independent equations:

[tex]\[ \begin{aligned} &1.\quad x + 2y - z = 3 \quad \text{(Equation 1)} \\ &4.\quad x + 2y = -4 \quad \text{(Equation 4)} \end{aligned} \][/tex]

Now, let's subtract Equation 4 from Equation 1 to eliminate [tex]\(x\)[/tex] and [tex]\(y\)[/tex]:

[tex]\[ (x + 2y - z) - (x + 2y) = 3 - (-4) \implies -z = 7 \implies z = -7 \][/tex]

We have found [tex]\(z = -7\)[/tex].

Next, let's substitute [tex]\(z = -7\)[/tex] back into Equation 4 to find [tex]\(x\)[/tex]:

[tex]\[ x + 2y = -4 \quad \text{(Equation 4)} \][/tex]

Since [tex]\(x = -2y - 4\)[/tex], substituting [tex]\(x\)[/tex] we get:

Finally, we only have this relation [tex]\(x = -2y - 4\)[/tex] holding true.

Therefore, the solutions are given by:

[tex]\[ \begin{aligned} &x = -2y - 4, \\ &z = -7 \end{aligned} \][/tex]

Here, [tex]\(y\)[/tex] can be any real number, making [tex]\(x\)[/tex] and [tex]\(z\)[/tex] dependent on [tex]\(y\)[/tex].